1989
DOI: 10.1111/j.1365-277x.1989.tb00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Foods eaten outside the home: nutrient contribution to total diet.

Abstract: The National Food Survey provides a valuable supply of information on the intake of food and nutrients in the British diet (Derry & Bus, 1984), but is confined to foods brought into the home. The present study examined nutrient contribution from foods eaten outside the home to the overall diet. Seventy subjects (35 males and 35 females), were selected from a local health centre register, using age and sex as criteria, and asked to keep a written record of everything consumed for three days. There was a very hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 1 publication
0
20
0
Order By: Relevance
“…Similar findings were reported in other studies. Loughridge et al 28 showed that meats and chips contributed 24% and 11%, respectively, to fat intake outside the home. This study is rather dated and it is possible that eating patterns may have changed; however, as there is a paucity of research in this area, it is important to make comparisons with papers that are available.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported in other studies. Loughridge et al 28 showed that meats and chips contributed 24% and 11%, respectively, to fat intake outside the home. This study is rather dated and it is possible that eating patterns may have changed; however, as there is a paucity of research in this area, it is important to make comparisons with papers that are available.…”
Section: Discussionmentioning
confidence: 99%
“…Some had a detailed breakdown of the FSS 2,6,9,13,14,36 , while other studies did not need to categorise the locations as they focused on fast food only 5,7 . None of the above studies analysed the possibility of underreporting, with only two studies acknowledging that it may need to be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size used in the various studies varied greatly from 70 respondents 13 to 63 880 respondents 36 , with the latter based on a number of surveys in the USA. Most of the studies had a population of between 1000 and 3500 respondents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…International studies have found that food eaten out of home tends to have a less healthy profile, e.g. a higher density of fat, saturated fat, sugar and alcohol, than food consumed at home (4,6,7) . Eating out of home has also been associated with obesity and weight gain (8)(9)(10)(11) .…”
mentioning
confidence: 99%